2010
DOI: 10.1080/17543261003627813
|View full text |Cite
|
Sign up to set email alerts
|

Body shape and fit preference in body cathexis and clothing benefits sought for professional African-American women

Abstract: Little survey research exists that categorises the body shapes of African-American women or attempts to understand how these impact their clothing choices. This study profiled 153 professional African-American women regarding the influence of body shape and fit preference on their perceptions of body cathexis (degree of satisfaction or dissatisfaction with one's body) (Secord, P. and Jourard, S., 1953. The appraisal of body cathexis: body cathexis and the self. Journal of Consulting Psychology, 17, 343-347) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…Chattaraman and Rudd (2006) had similar findings—increases in body size among women correlated with preferences for tops with looser fits. With respect to age, Manual et al (2010) similarly found that female participants in their 20s preferred a fitted jacket, whereas those in their 30s picked a loose fit.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Chattaraman and Rudd (2006) had similar findings—increases in body size among women correlated with preferences for tops with looser fits. With respect to age, Manual et al (2010) similarly found that female participants in their 20s preferred a fitted jacket, whereas those in their 30s picked a loose fit.…”
Section: Discussionmentioning
confidence: 86%
“…This procedure was repeated for each garment type and ensured that the men evaluated garment fit based on perceptual analysis of fit classifications for each garment type. The scale merges two methods: one developed by Chattaraman and Rudd (2006) and another depicting 3 levels of fit variations in specific women’s style types (Alexander et al, 2005; Fu, 2004; Manuel et al, 2010; Pisut & Connell, 2007). A pilot study with 5 male students enrolled at the university (recruited through snowball sampling) was conducted to assess the comprehensibility and clarity of the questions and validity of the various measures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that, 37% of Turkish women had hourglass, 31% had triangle, 19% had rectangle and 13% had an inverted triangle body shape [8]. Manuel et al (2010) categorized the body shapes of African-American women in their study and examined how these body shapes affected women's clothing preferences [9]. Vuruşkan and Bulgun (2011) asserted that the methods used currently to determine the female body shapes generally depended on subjective and visual decision-making approaches.…”
Section: Clothing Fit Is One Of the Most Important Factors That Affecmentioning
confidence: 99%
“…While many studies of fit perception were conducted with either female or male consumers, Shin (2013) qualitatively investigated gender differences in overall fit satisfaction and fit problems and experiences. In Shin's (2013) study, while both male and female young consumers were neutral to slightly satisfied with fit regarding ready-to-wear clothing in general and all three dimensions of fit were used by both male and female participants to describe fit, male participants were more likely to report fit problems in physical and functional aspects while female participants tended to mention aesthetic fit problems more frequently, especially those related to attractiveness Furthermore, previous studies on fit satisfaction and fit preference related to age showed that older women had greater dissatisfaction with garment fit (Plutt, 2011;Shim & Bickle, 1993) and preferred loose fit (Howarton & Lee, 2010;Manual, Connell, & Presley, 2012;Pisut & Connell, 2007;Simmons & Istook, 2003). Plutt (2011) found that women's age was negatively related with their fit satisfaction, indicating that the degree of fit satisfaction decreased as age increased.…”
Section: Exploratory Research Questionsmentioning
confidence: 88%